2016
DOI: 10.1186/s12906-016-1418-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of allergic rhinitis with acupoint herbal plaster: an oligonucleotide chip analysis

Abstract: BackgroundAllergic rhinitis is regarded as an imbalanced Th1/Th2 cell-mediated response. The present study used microarray analysis to compare gene expression levels between allergic rhinitis patients before and after a series of acupoint herbal plaster applications.MethodsIn this experimental pilot study, volunteers experiencing sneezing, runny nose, and congestion for more than 9 months in the year following initial diagnoses were included after diagnostic confirmation by otolaryngologists to exclude patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…Furthermore, IL-13 immune response was downregulated in that particular group of patients. [ 22 ] Similarly, another study demonstrated the effectiveness of subcutaneous injectable immunotherapy in treating the sinus inflammation and pain in 281 allergic rhinitis patients. The subcutaneous immunotherapy as treatment of allergic rhinitis led to a reduction in all symptoms studied, improving the QoL of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, IL-13 immune response was downregulated in that particular group of patients. [ 22 ] Similarly, another study demonstrated the effectiveness of subcutaneous injectable immunotherapy in treating the sinus inflammation and pain in 281 allergic rhinitis patients. The subcutaneous immunotherapy as treatment of allergic rhinitis led to a reduction in all symptoms studied, improving the QoL of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In other Asian countries such as China and Japan, facial candling is practised in the form of moxibustion where burning cigar-shaped dried mugwort stick is used to warm regions and meridian points. [ 22 ] Facial candling treatments are believed to give various impacts to the patients, including reducing stress as it promotes relaxation, and reduces headache, ear, or throat infection. [ 23 ] Furthermore, the facial candling technique is said to improve the blood circulation throughout the whole body and reduce symptoms of allergic rhinitis.…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the action mechanisms of the plants used at acupoints indicated that acupoint herbal plaster improved allergic inflammation via maintaining an appropriate balance between Th1 and Th2 cells and therefore inhibited the secretion of cytokines GM-CSF, IL-3, IFN-γ, and IL-2 by Th1 cells and that of IL-3, GM-CSF, IL-13, IL-10, IL-5, and IL-4 by Th2 cells 57,58 . These cytokines contribute to activation of JAK-STAT (regulator of activity of histamine mediators).…”
Section: Bregmentioning
confidence: 99%
“…For example, IL-13, which is one of the lymphocytes of Th2 and produces ILC2, plays a key role in exacerbating inflammatory response such that humanized monoclonal antibody against the fixed part of IL-13 was found to be greatly effective in improving allergy. A study demonstrated that plant-based compounds induced anti-inflammatory and antiallergy effects through down regulating IL-13 via JAK-STAT pathway 57 . Actually medicinal plants through several mechanisms can prevent the allergic rhinitis (Fig.…”
Section: Bregmentioning
confidence: 99%
“…In TCM, disease is understood to originate from an imbalance or poor flow of qi. Acupuncture has long been used in TCM to treat AR, and studies of this treatment have shown mixed results, with the most rigorous studies showing only modest clinical benefits [21][22][23][24]. The 2015 revision of the American Academy of Otolaryngology-Head and Neck Surgery clinical practice guidelines for AR cites a low level of confidence in the evidence to support acupuncture as a treatment option.…”
Section: Introductionmentioning
confidence: 99%